The Effect of Yijinjing on the Cognitive Function of Patients With Chronic Schizophrenia - Gao, Hui; Luo, Chao; Tu, Si-Jing; Lu, Ru-Ping; Jiang, Lin-Na; Qiao, Hui-Jun; Lin, Qu; Li, Ning-Ning; Chen, Jian-Hua (Frontiers in Psychiatry, 2021)
Background: Patients with chronic schizophrenia present cognitive impairment, which affects their social function and prevents them from reintegrating into society. Yijinjing is a traditional Chinese aerobic exercise that has a putative psychosomatic effect on improving cognitive function. Methods: From January to May 2021, 40 patients with chronic schizophrenia were recruited and randomly divided into a control group and a Yijinjing group. In the 12-week intervention, the patients in the control group received conventional treatment, whereas patients in the Yijinjing group performed Yijinjing exercise (40 min/session, twice a week) in addition to receiving conventional treatment. The Positive and Negative Syndrome Scale (PANSS), the Insight and Treatment Attitude Questionnaire (ITAQ), the Rosenberg Self-esteem Scale (SES), and the Mini Mental State Examination (MMSE) were used to measure clinical symptoms and cognitive function at 0, 6, and 12 weeks. Results: The demographic information was not significantly different between groups. At baseline, the scores of all the scales were not statistically different between groups. After 12 weeks of intervention, compared to those at baseline, the scores of the negative scale (t = 19.00, p < 0.0001), general psychopathology scale (t = 15.98, p < 0.0001), and total score (t = 15.47, p < 0.0001) of the PANSS and SES (t = 5.378, p < 0.0001) had significantly decreased, and the scores of the ITAQ (t = 7.984, p < 0.0001) and MMSE (t = 6.750, p < 0.0001) had significantly increased in Yijinjing group; the score of the MMSE increased in the control group as well (t = 2.491, p = 0.0222). Compared to the respective scores in the control group, the negative scale score (t = 2.953, p = 0.0054) significantly decreased, and the ITAQ (t = 3.043, p = 0.0042) and MMSE (t = 2.2.68, p = 0.0291) scores significantly increased in the Yijinjing group after 12 weeks of intervention. Conclusion: These results provide a preliminary indication that Yijinjing exercise had the potential to improve cognitive function and negative symptoms in patients with chronic schizophrenia. A larger-scale study to determine the trajectory of change in the longer term should be undertaken.